PENINGKATAN PERILAKU DISIPLIN SISWA MELALUIPEMBERIAN REWARD DAN PUNISHMENT DALAM PEMBELAJARAN PENJASORKES PADA SISWA KELAS XII IPS 1 SMA NEGERI 1 LAMONGAN - INDRAWATI, RENGGA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical sport and health education is one of the subjects which is on the all of educational grade that is assumed create the people not only to be physically healthy but also in morality. The elements of moral education that become the responsibility in physical sport and health educational subject are on the creation of performing high supportive point, one of them is obedient discipline behavior. Discipline behavior is the basic standart of creating good and simple Indonesians moral. So, discipline should be applicated everywhere and everytime. Hopefully, the method that usedto increase student’s discipline behavior is implementation  of giving gift and punishment which is usually called reward and punishment. Goal of this research is to increase student’s discipline by giving reward and punishment in physical sport and health educational subject. This research uses class action research which are done by giving treatment to the participants on one cycle. Participants are the students of XII Social Science 1 SMA Negeri 1 Lamongan which is consists of 34 students, 18 males and 16 females. The instrument used to know about progress of student’s discipline are present report sheet, researcher conclusion note observation sheet, and reliable and valid questionnaire. Based on the result of this research, it is known that student’s disciplin behavior increasing by completing all of the indicators which is decided as arranging of the instruments is 84,96% from minimum limitation which decided is 75%. So, generally it can be concluded that the implementation of giving reward and punishment on physical sport and health educational subject can increase student’s discipline. Keywords: student’s discipline behavior, reward and punishment